1993
DOI: 10.1246/bcsj.66.927
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of a New Fluorescent Barbiturate Receptor. Sensitive Detection of Barbiturates through Solvent Extraction

Abstract: A fluorescent receptor, N,N′-bis[6-[4-(1-pyrenyl)butanamido]-2-pyridyl]isophthalamide (2), was synthesized to develop a sensitive host–guest-type sensory system for barbiturates. 2 aggregates in cyclohexane and the pyrene fluorescence in 2 almost disappeared because of aggregation-induced concentration quenching. The addition of barbital to the cyclohexane solution of 2, which induced the deaggregation of 2 through complementary complexation with barbital, increased the fluorescence intensity at 378 nm by a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The excited-state interaction between two 1-pyrenyl fluorophores can also be attenuated by barbiturate binding to the central bis(2,6-diaminopyridine) receptor (cf. 45 and 225 in sections VI.A and X, respectively) of 226 in homogeneous or two-phase solution. This principle is general enough to encompass trifluorophoric systems based on C 3 symmetric calix[6]arenes and partial cone conformations of homotrioxacalix[3]arenes which target guanidinium and primary alkylammonium ions respectively.…”
Section: Monomer−excimer Systemsmentioning
confidence: 99%
“…The excited-state interaction between two 1-pyrenyl fluorophores can also be attenuated by barbiturate binding to the central bis(2,6-diaminopyridine) receptor (cf. 45 and 225 in sections VI.A and X, respectively) of 226 in homogeneous or two-phase solution. This principle is general enough to encompass trifluorophoric systems based on C 3 symmetric calix[6]arenes and partial cone conformations of homotrioxacalix[3]arenes which target guanidinium and primary alkylammonium ions respectively.…”
Section: Monomer−excimer Systemsmentioning
confidence: 99%
“…Hamilton et al reported that complexation of cyclic and acyclic receptors bearing two diamidopyridine units linked through an isophthaloyl spacer with barbituric acids via six hydrogen bonds in apolar organic solvents such as chloroform and dichloromethane. 3 Similar binding motifs bearing redox active, 4 chiral 5 metal ligand, 6 and chromophore 7 moieties have also been reported as barbiturate and cyanurate receptors. The diamidopyridine group was applied to construct more sophisticated materials such as supramolecular polymers.…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, derivatized Hamilton receptors that contain fluorogenic and other chromophoric groups are needed. Toward these aims, prior work by Aoki et al demonstrated that appending pyrene moieties to an acyclic Hamilton receptor results in a strong fluorescence turn-on that can be monitored by fluorescence spectroscopy . The efficacy of this system is largely due to solvent effects that cause disaggregation of the host molecule in the presence of barbiturates.…”
Section: Introductionmentioning
confidence: 99%